Phase II study of compensator-based non-coplanar intensity-modulated radiotherapy for Stage I non–small-cell lung cancer. (11th April 2019) - Itonaga, Tomohiro; Mikami, Ryuji; Nakayama, Hidetsugu; Saito, Tatsuhiko; Shiraishi, Sachika; Okubo, Mitsuru; Sugahara, Shinji; Ikeda, Norihiko; Tokuuye, Koichi
Abstract: We conducted a Phase II study to evaluate the usefulness of compensator-based non-coplanar intensity-modulated radiotherapy (ncIMRT) for patients with surgically inaccessible Stage I non–small-cell lung cancer (NSCLC). Patients with pathologically proven or clinically diagnosed surgically inaccessible Stage I NSCLC were enrolled in this study from May 2011 to April 2014. These patients underwent ncIMRT of 75 Gy in 30 fractions regardless of the tumor location. The primary end point was 3-year overall survival, and the secondary end points were local control rate and treatment-related toxicities. A total of 48 patients (50 tumors) were enrolled in this study. Of the 50 tumors, the Stage T1 to T2 ratio was 31 to 19, and the ratio of tumors located in the central to peripheral areas was 11 to 39. During the median follow-up time of 35.9 months, the 3-year actuarial local progression-free and overall survival rates were 82.6% and 87.1%, respectively. No patients experienced toxicities of Grade 3 or greater. Standard-fractionated ncIMRT was effective and safe for patients with surgically inaccessible stage I NSCLC, regardless of the tumor location.